AN INVESTIGATION INTO THE RELATIONSHIP BETWEEN ENTREPRENEURIAL ORIENTATION AND STRATEGIC LEARNING CAPABILITY IN THE SELECTED NIGERIAN PUBLIC SECTOR - Ifere, Simeon E.; Fajimolu, Oladimeji C.; Ebegbetale, Christopher I. (Covenant Journal of Entrepreneurship, 2022)
This study examines the association between entrepreneurial orientation and strategic learning capability using organic structure, market responsiveness and mode of strategy formation as mediating variable. It explicates how public organisations generate strategic knowledge and use such knowledge to enhance their business operations. Using a survey design, 450 questionnaires were distributed among 12 governmental agencies and 228 questionnaires were retrieved. The data were analyzed using regression analysis. The findings indicate a strong association between entrepreneurial orientation and strategic learning capability. Also, when the mediating variables were simultaneously entered with the independent variable as a predictor of strategic learning capability, they all made the criterion variable stronger and show that the relationships are statistically significant. The study concludes that being entrepreneurially oriented in public organisations will lead to strategic learning capability and recommends that managers consciously and actively encourage policies and actions that are entrepreneurial in order to foster strategic learning capability, strategic change and organisational effectiveness.